Developing Animated Videos-Based Teaching Materials for Creative Writing Learning: Short Story Building Blocks - Taqwiem, Ahsani; Luthfiyanti, Lita (Indonesian Journal of Multidisciplinary Science, 2023)
This research aims to serve the development of teaching materials based on Powtoon animation videos for learning creative writing material for building short stories. The ADDIE (Analysis, Design, Development, Implementation, and Evaluation) model was used to develop these materials. The needs analysis phase was carried out using an electronic form and received 52 completed questionnaires. The validation results of two experts show that the media and animated video material are very valid and can be used as a learning medium for writing short stories with an average score of 96%. It is hoped that the development of teaching materials based on Powtoon animated videos can support a more effective and interesting learning process, especially for Generation Z who grew up amid technological advances and learn by observing visually.